Dampak Digital Ekonomi Melalui Platform E- Commerse Terhadap Ketahanan Keuangan pada UMKM di Pasar Menganti - Della Erdiana; Nur Fitroten Dian Sari; Ayu Asari; Maria Yovita R. Pandin (Economic Reviews Journal, 2024)
Menganti Market, a traditional market in Gresik, East Java, is feeling the impact of economic digitalization through e-commerce platforms on MSMEs in the market. This causes a decrease in turnover and unbalanced MSME business competition. Financial literacy and adaptation to digital technology are key in facing this change. Traders experienced a decline in income due to changes in people's shopping styles to e-commerce. Online and offline trade should be supported by policies that do not harm other parties, according to traders. In conclusion, the development of the digital economy poses significant challenges to traditional markets, as does the requirement for regulations that ensure the long-term viability of traditional traders' businesses.